Workplace Violence among Nurses - Kalikote, Bhagawati (Journal of Nursing Education of Nepal, 2023)
Introduction: Work Place Violence (WPV) is a issue faced by the nursing professionals all over the world. Systematic review findings have added insight for addressing the issue.Methods: A total of 40 original and reviewed articles were searched through electronic databases like Pubmed, Google Scholar and Research Gate. Among them, 21 relevant articles (14 original research & 9 review articles) were selected and analyzed, cited and prepared a reference list by using Zotero software. After thoroughly reviewing those articles related to workplace violence were summarized.Results: A total of 23 articles were included. The majority of the studies showed that Nurses are at great risk of violence because of the nature of their work and the usual contact with patients and their relatives. Most of the cases are not handled and reported properly and these incidents include verbal abuse, physical assault, bullying/mobbing and sexual harassment. Verbal violence is commonly compared with physical abuse and sexual harassment. WPV is directly related to decreasing job satisfaction, burnout, humiliation, guilt, emotional stress, intention to quit a job, and increased staff turnover. A significant proportion of nurses faced violence while providing care at health facilities.Conclusion: Intervention is needed to protect nurses and provide them safe hospital workplace environment. Nurses should be educated appropriately on hospital policies against WPV and be encouraged to report any incidence.DOI: https://doi.org/10.62143/vadtws15